2020
DOI: 10.1177/2059204320938635
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Emotions of Harmonic Cadences

Abstract: Harmonic cadences are chord progressions that play an important structural role in Western classical music – they demarcate musical phrases and contribute to the tonality. This study examines participants’ ratings of the perceived arousal and valence of a variety of harmonic cadences. Manipulations included the type of cadence (authentic, plagal, half, and deceptive), its mode (major or minor), its average pitch height (the transposition of the cadence), the presence of a single tetrad (a dissonant four-tone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Second, it allowed us to present probabilistic evidence for the presence or absence of an effect rather than to report only a binary test for the null hypothesis as is done in frequentist approaches. We have successfully used our Bayesian modeling approach in previous studies where we could not apply frequentist statistics due to the small number of participants (Escudero et al, 2020) or where research questions and data were better handled with probabilistic evidence (Smit et al, 2019(Smit et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it allowed us to present probabilistic evidence for the presence or absence of an effect rather than to report only a binary test for the null hypothesis as is done in frequentist approaches. We have successfully used our Bayesian modeling approach in previous studies where we could not apply frequentist statistics due to the small number of participants (Escudero et al, 2020) or where research questions and data were better handled with probabilistic evidence (Smit et al, 2019(Smit et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the present results paint a clear picture about music’s ability to influence directed imagination, the driving forces behind the observed effects remain unclear. Music’s ability to generate predictions 64 , 65 , convey emotion 66 68 , as well as its resilience to forgetting 69 , 70 paired with its capacity to evoke autobiographical memories 71 would all be prime candidates. Additionally, cross-modal studies have shown that the neural activity in the early visual cortex can be used to classify heard and imagined sounds, as well as their emotional connotation 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to these limitations, we opted to use discrete chords rather than continuous musical pieces to explore their effects on declarative learning. By doing so, we were able to account for particular musical elements related to the consonance-dissonance continuum, as well as perceived pleasantness (valence), and acoustical elements such as sound roughness 49 .…”
Section: Discussionmentioning
confidence: 99%